1985
DOI: 10.1093/ajcn/42.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of transsulfuration pathway products during nasoenteral and intravenous hyperalimentation of malnourished patients

Abstract: We have monitored the plasma concentrations of products of the transsulfuration pathway in 11 undernourished noncirrhotic patients, and in 10 cachectic cirrhotic subjects, before and during nasoenteral nutrition with Vivonex (Norwich-Eaton Pharmaceuticals, Norwich, NY) or total parenteral nutrition (TPN) with FreAmine III (American McGaw, Irvine, CA). In the cirrhotic cases eating a mixed diet, levels of taurine, cysteine, plasma glutathione, and free choline were subnormal. During nasoenteral hyperalimentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…There is some evidence to support that this choline deficiency plays a role in the hepatic impairment seen in patients on longterm PN. Enteral repletion of choline to prevent or treat PN-induced hepatic failure is currently under research and shows a lot of promise [53].…”
Section: Amino Acids On the Horizonmentioning
confidence: 99%
“…There is some evidence to support that this choline deficiency plays a role in the hepatic impairment seen in patients on longterm PN. Enteral repletion of choline to prevent or treat PN-induced hepatic failure is currently under research and shows a lot of promise [53].…”
Section: Amino Acids On the Horizonmentioning
confidence: 99%
“…Lipid emulsion supplied a very minimal amount of choline (24 Ϯ 6 nmol/mL) and therefore is an inadequate source of choline for patients requiring long-term home TPN. 25 Chawla et al 40 …”
Section: Prevalence Of Low Plasma Choline Concentration In Tpn Patienmentioning
confidence: 99%
“…39 It was also assumed that this nutrient could be synthesized from methionine (contained in the TPN solution) through the hepatic transsulfuration pathway. However, several studies have suggested that the transsulfuration pathway is impaired or nonfunctional in patients receiving TPN; 24,40 choline deficiency may result. The Food and Nutrition Board of the National Academy of Sciences designated an adequate intake for choline in 1998 for the first time.…”
mentioning
confidence: 99%
“…methionine has been shown to be inhibited during TPN. 36 Additionally, sulfoester excretion products have been shown to decrease in infants receiving a TPN diet that was deficient in inorganic sulfate but not sulfur-containing amino acids.37 Therefore, it is possible that decreased PAPS availability could be responsible for the observed decrease in sulfation during TPN. Plasma sulfate concentrations measured before acetaminophen administration, however, were higher in the group receiving TPN, suggesting that initial sulfate availability was not a factor in the decrease in acetaminophen sulfation seen in vivo in the TPN animals.…”
Section: Table IIImentioning
confidence: 99%